El espiritismo y los elementos religiosos africanos y aborígenes del etnos. Su discriminación colonial y neocolonial en Cuba - Ortega Suárez, Jorge Domingo; Mercadet Portillo, Nancy Narcisa (Comparative Cultural Studies - European and Latin American Perspectives, 2022)
The article identifies the possible geographical routes to entrance to Cuba of modern spirit beliefs during the second half of the 19th century. Exposes the Cuban international and historical-concrete conditions to the reception of modern spirit beliefs in this country and the causes of the prevalence of the Kardecist spiritism in the Cuban territory, among various causes due to its possible sincresis with religious elements of certain components of ethnos, aborigines included and specially the Africans, with which the spiritism share the emphasis on their defense of reincarnation, the importance given to sensory impressions and to facilitating the cathartic processes of the subject; the intelligibility of its basic worldview for all population segments, the immediacy of results it promises and the subject’s unrestricted access to mediumship. The article also explains the causes of political, legal, and even confessional rejection from colonial and republican neocolonial governments allied with empowerment religious institutions respect to the entry, establishment and institutionalization of modern spirit beliefs in Cuba.